TRAF Regulation of IL-17 Cytokine Signaling - Swaidani, Shadi; Liu, Caini; Zhao, Junjie; Bulek, Katarzyna; Li, Xiaoxia (Frontiers in Immunology, 2019)
Tumor necrosis factor receptor (TNFR)-associated factors or (TRAFs) are important mediators of Interleukin-17 (IL-17) cytokine signaling and contribute to driving tissue responses that are crucial for protective immunity but are often implicated in immunopathology. By amplifying tissue immune activity, IL-17 cytokine pathways contribute to maintaining barrier function as well as activation of innate and adaptive immunity necessary for host defense. IL-17 receptors signaling is orchestrated in part, by the engagement of TRAFs and the subsequent unlocking of downstream cellular machinery that can promote pathogen clearance or contribute to immune dysregulation, chronic inflammation, and disease. Originally identified as signaling adaptors for TNFR superfamily, TRAF proteins can regulate the signaling of a variety of intercellular and extracellular stimuli and have been shown to regulate the downstream activity of many cytokine receptors including receptors for IL-1β, IL-2, IL-6, IL-17, IL-18, IL-33, type I IFNs, type III IFNs, GM-CSF, M-CSF, and TGF-β, Toll-like receptors (TLRs), NOD-like receptors (NLRs), RIG-I-like receptors, and C-type lectin receptors. This review will focus on discussing studies that reveal our current understanding of how TRAFs mediate and regulate biochemical activities downstream of the IL-17 family cytokines signaling.